Biochemical and Molecular Characterization of a Novel UDP-Glucose:Anthocyanin 3′-O-Glucosyltransferase, a Key Enzyme for Blue Anthocyanin Biosynthesis, from Gentian - Fukuchi-Mizutani, Masako (The American Society for Plant Biologists, 2003)
Gentian (Gentiana triflora) blue petals predominantly contain an unusually blue and stable anthocyanin, delphinidin 3-O-glucosyl-5-O-(6-O-caffeoyl-glucosyl)-3′-O-(6-O-caffeoyl-glucoside) (gentiodelphin). Glucosylation and the subsequent acylation of the 3′-hydroxy group of the B-ring of anthocyanins are important to the stabilization of and the imparting of bluer color to these anthocyanins. The enzymes and their genes involved in these modifications of the B-ring, however, have not been characterized, purified, or isolated to date. In this study, we purified a UDP-glucose (Glc):anthocyanin 3′-O-glucosyltransferase (3′GT) enzyme to homogeneity from gentian blue petals and isolated a cDNA encoding a 3′GT based on the internal amino acid sequences of the purified 3′GT. The deduced amino acid sequence indicates that 3′GT belongs to the same subfamily as a flavonoid 7-O-glucosyltransferase from Schutellaria baicalensis in the plant glucosyltransferase superfamily. Characterization of the enzymatic properties using the recombinant 3′GT protein revealed that, in contrast to most of flavonoid glucosyltransferases, it has strict substrate specificity: 3′GT specifically glucosylates the 3′-hydroxy group of delphinidin-type anthocyanins containing Glc groups at 3 and 5 positions. The enzyme specifically uses UDP-Glc as the sugar donor. The specificity was confirmed by expression of the 3′GT cDNA in transgenic petunia (Petunia hybrida). This is the first report of the gene isolation of a B-ring-specific glucosyltransferase of anthocyanins, which paves the way to modification of flower color by production of blue anthocyanins.